2003
DOI: 10.1046/j.1525-1594.2003.07190.x
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Analysis of an Intra‐Cardiac Axial Flow Pump

Abstract: A low rate of hemolysis is an important factor for the development of a rotary blood pump. It is, however, difficult to identify the areas where hemolysis occurs. Computational fluid dynamics (CFD) analysis enables the engineer to predict hemolysis on a computer. In this study, fluid dynamics throughout intracardiac axial flow pumps with different designs were analyzed three-dimensionally using CFD software. The computed pressure-flow characteristics of the pump were in good agreement with the measurements. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 12 publications
0
61
0
Order By: Relevance
“…Antaki 1 also discussed the utility of power-law models and concluded that they are unable to capture the effects of subtle features of the blood contacting geometry, which have been shown to largely affect hemolysis. Previous researchers have attempted to use current blood damage power-law models to estimate hemolysis from CFD results, often using a Lagrangian approach, 22,33,45 where damage was calculated along multiple streamlines in the domain of interest. These conventional models provide poor estimates of hemolysis when compared to experimental hemolysis data in the same flow system, thus these investigators have illustrated the inaccuracy of current models for hemolysis prediction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antaki 1 also discussed the utility of power-law models and concluded that they are unable to capture the effects of subtle features of the blood contacting geometry, which have been shown to largely affect hemolysis. Previous researchers have attempted to use current blood damage power-law models to estimate hemolysis from CFD results, often using a Lagrangian approach, 22,33,45 where damage was calculated along multiple streamlines in the domain of interest. These conventional models provide poor estimates of hemolysis when compared to experimental hemolysis data in the same flow system, thus these investigators have illustrated the inaccuracy of current models for hemolysis prediction.…”
Section: Introductionmentioning
confidence: 99%
“…19,31,33 Lokhandwalla and Sturtevant, 31 for example, noted the presence of extensional flow with hemolysis from shock wave lithotripsy. When working with hamster ovary cells, Mollet et al 34 found that high levels of cell damage were seen in areas of high extensional stress.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the advantages of the k-ε model are robustness, reasonable accuracy for wide flow ranges, and computational economy [1,3]. The k-ε model has been commonly used to design prosthetic heart devices [49][50][51][52][53][54]. For the k-ω turbulence model, the shear-stress transport (SST) k-ω model was used.…”
Section: Turbulence Modelmentioning
confidence: 99%
“…More recently, hemolysis predictions on heart valves and blood pumps have been made by several research groups, using the results of CFD analysis. [1][2][3][4][5][6][7] These studies incorporate blood cell damage models based upon a power-law relationship among hemoglobin release, shear stress, and exposure time. 8,9 Consideration of hemolysis as a function of shear stress and exposure time is a conventional approach.…”
Section: Computational Fluid Dynamics (Cfd) Simulations On a Varietymentioning
confidence: 99%